Beppu Bay, Japan, as a candidate Global boundary Stratotype Section and Point for the Anthropocene series. (April 2023) - Kuwae, Michinobu; Finney, Bruce P; Shi, Zhiyuan; Sakaguchi, Aya; Tsugeki, Narumi; Omori, Takayuki; Agusa, Tetsuro; Suzuki, Yoshiaki; Yokoyama, Yusuke; Hinata, Hirofumi; Hatada, Yoshio; Inoue, Jun; et al.
For assessment of the potential of the Beppu Bay sediments as a Global boundary Stratotype Section and Point (GSSP) candidate for the Anthropocene, we have integrated datasets of 99 proxies. The datasets for the sequences date back 100 years for most proxy records and 1300 years for several records. The cumulative number of occurrences of the anthropogenic fingerprint reveal unprecedented increases above the base of the 1953 flood layer at 64.6 cm (1953 CE), which coincides with an initial increase in global fallout of 239 Pu+ 240 Pu. The onset of the proliferation of anthropogenic fingerprints was followed by diverse human-associated events, including a rapid increase in percent modern 14 C in anchovy scales, changes in nitrogen and carbon cycling as recorded by anchovy δ 15 N and δ 13 C, elevated pollution of heavy metals, increased deposition of novel materials (spheroidal carbonaceous particles, microplastics, polychlorinated biphenyls), the occurrence of hypoxia (Re/Mo ratio) and eutrophication (biogenic opal, TOC, TN, diatoms, chlorophyll a), unprecedented microplankton community changes (compositions of carotenoids, diatoms, dinoflagellates), abnormally high spring air temperatures as inferred from diatom fossils, and lithological changes. These lines of evidence indicate that the base of the 1953 layer is the best GSSP level candidate in the stratigraphy at this site.